Natural history of lung function over one year in patients with Parkinson's disease. (June 2021) - Kaminsky, David A.; Grosset, Donald G.; Kegler-Ebo, Deena M.; Cangiamilla, Salvador; Klingler, Michael; Zhao, Ping; Oh, Charles
Abstract: Background: Little is known about decline in lung function in Parkinson's disease (PD). To assess these changes, we assessed the changes in lung function that occurred over 12 months in patients on standard PD therapy as part of the observational cohort of an open-label study of inhaled levodopa (CVT-301) in PD. Methods: PD patients on stable oral PD therapy and no chronic respiratory disease had spirometry and diffusing capacity of the lungs for carbon monoxide (DLCO ) measured at 3, 6, 9, and 12 months. Results: 106 patients (81.5%) in the observational cohort on no investigational therapy completed the study. Mean FEV1 declined at 12 months from 2.88L at baseline with a mean change of −0.11L, greater than the −0.030–0.045L/year observed in healthy, non-smokers aged 60–70 years. FVC declined from 3.77L (mean change −0.19L); FEV1 /FVC ratio remained relatively constant. DLCO mean change was −0.48 mL/min/mmHg from a baseline of 24.24 mL/min/mmHg. This change in DLCO, while not significant, was similar to that seen in non-smokers aged 60–70 years (DLCO -0.42–0.63 mL/min/mmHg/year). Decreases in alveolar volume (VA) and inspiratory vital capacity (IVC) rather than the transfer coefficient (DLCO /VA) were observed. Conclusions: PD patients had greater declines in FEV1, and FVC, but not in DLCO, compared to healthy non-smokers of similar age. Declines in FEV1 and FVC with little change in FEV1 /FVC, and decline in VA and IVC with little change in DLCO /VA, suggest these changes were due to decreases in lung volume and are compatible with progressive PD-associated respiratory muscle weakness. Trial registration: ClinicalTrials.gov (NCT02352363 Registered January 26, 2015 [https://clinicaltrials.gov/ct2/show/NCT02352363 ]) and EudraCT (2014-003799-22). Highlights: We examined the lung function of patients with Parkinson's Disease over one year. Patients had greater declines in FEV1 and FVC, but not in DLCO, than healthy people. The results were consistent with decreases in lung volume over time. This finding is compatible with progressive respiratory muscle weakness.